Phytochemical comparison and evaluation of anti-inflammatory and anti-diabetic activity of three source plants of Jivanti-an important Ayurvedic drug - Sulaiman C. T.; Jyothi C. K.; Jinu Krishnan Unnithan G.; Prabhukumar K. M.; Indira Balachandran (SpringerOpen, 2021)
Abstract Background In Ayurveda, Jivanti is an important Rasayana drug that increases the energy level of the body. The botanical source of Jivanti is in a situation of controversy. The root of Leptadenia reticulata is the genuine source plant for Jivanti as per Ayurvedic Pharmacopeia of India. However, other species such as Holostemma ada-kodien and Flickingeria nodosa are also used as source plants for Jivanti in various parts of the country. The objective of this study is to identify a scientifically validated alternative source plant for Jivanti by phytochemical and pharmacological evaluation. Results In this study, anti-inflammatory and anti-diabetic activities of various source plants for Jivanti were evaluated along with their phytochemical comparison. H. ada-kodien showed significant anti-inflammatory and anti-diabetic activity when compared to L. reticulata. Conclusion The study concluded the possibility of using Holostemma ada-kodien as a substitute for Jivanti in the Ayurvedic drug industry. Graphical abstract